2012
DOI: 10.1113/expphysiol.2011.061960
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that angiotensin‐(1–7) is an intermediate of gonadotrophin‐induced oocyte maturation in the rat preovulatory follicle

Abstract: Several studies have shown the presence of components of the renin-angiotensin system in mammalian ovaries and their involvement in ovarian physiology. We have previously shown the presence of angiotensin-(1-7) [Ang-(1-7)], an important biologically active component of the renin-angiotensin system, and its receptor, Mas, in rat, rabbit and human ovaries. We have also shown the involvement of Ang-(1-7) in the rabbit ovulatory process in vitro. In the present study, we observed that Ang-(1-7) stimulated the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 52 publications
(81 reference statements)
2
43
0
1
Order By: Relevance
“…Consistent with a regulatory role of MAS in ovary, the MAS antagonist A-779 was shown to prevent breakdown of germinal vesicle and reduced oocyte maturation induced by Ang(1-7) (Honorato- Sampaio et al, 2012). Expression of MAS in uterus and placenta is thought to be relevant to diseases such as preeclampsia (Velloso et al, 2007).…”
Section: State Of the Angiotensin Receptorsmentioning
confidence: 81%
“…Consistent with a regulatory role of MAS in ovary, the MAS antagonist A-779 was shown to prevent breakdown of germinal vesicle and reduced oocyte maturation induced by Ang(1-7) (Honorato- Sampaio et al, 2012). Expression of MAS in uterus and placenta is thought to be relevant to diseases such as preeclampsia (Velloso et al, 2007).…”
Section: State Of the Angiotensin Receptorsmentioning
confidence: 81%
“…Male mice fed with a high-fat diet showed a decreased ACE2 expression in the kidney, resulting in reduced angiotensin (1-7) and increased angiotensin (1-8) levels. This caused blood hypertension that was reversed by the administration of losartan [14]. The same authors had previously shown a low expression of ACE2 in the adipose tissue of male mice [15].…”
Section: Abstract: Sars-cov2; Covid-19; Ace2: Venous Thromboembolism;mentioning
confidence: 82%
“…ACE2 has also been described in ovarian granulosa cells and its expression increases with a rise in luteinizing hormone (LH). Indeed, stimulation with human chorionic gonadotropic (hCG) improves the ACE2-angiotensin (1-7)-Mas system [14]. This may represent a compensatory mechanism that could be useful for avoiding an increase in blood pressure in postmenopausal women [15].…”
Section: Abstract: Sars-cov2; Covid-19; Ace2: Venous Thromboembolism;mentioning
confidence: 99%
“…The presence of ANG-(1-7) in the ovary was initially described by Costa et al in 2003 (100). These authors also were the first to suggest an involvement of the ANG-(1-7) peptide in pre-and postovulatory events, demonstrating higher levels of ANG-(1-7) in the proestrus and estrus as well as in equine chorionic gonadotropin (eCG)-treated rats (254). Later, the same group demonstrated that the ACE2/ ANG-(1-7)/MAS axis is fully expressed in rat ovaries (419) and in all stages of follicular development in humans (436).…”
Section: Female Reproductive Systemmentioning
confidence: 97%